One Aldwych, London: combining sustainability with luxury - Nicholas, Andrea (Henry Stewart Talks, 2017)
This case study highlights the achievements of the One Aldwych Hotel in its commitment to green tourism. Through initiatives like waste reduction, heat recovery and environmentally friendly products, One Aldwych has become a showcase for sustainable tourism in London.